Palladium-catalyzed enantioselective alkenylation of alkenylbenzene derivatives. Issue 30 (21st June 2019) - Chen, Zhi-Min; Liu, Jianbo; Guo, Jing-Yao; Loch, Maximillan; DeLuca, Ryan J.; Sigman, Matthew S.
Abstract : A regioselective and enantioselective palladium-catalyzed relay Heck alkenylation of alkenylbenzene derivatives to construct remote stereocenters is disclosed. Abstract : A regioselective and enantioselective palladium-catalyzed relay Heck alkenylation of alkenylbenzene derivatives to construct remote stereocenters is disclosed. Various β-substituted styrenes were readily obtained in moderate yields with good to excellent levels of enantioselectivity. This strategy provides rapid access to enantioenriched δ, ε, ζ, and η-alkenyl aryl compounds from simple starting materials. Mechanistic studies suggest that termination of the relay reaction is controlled by affinity of the arene for the Pd complex during migration.